Advanced and multifaceted stability profiling of the first-line antidiabetic drugs metformin, gliclazide and glipizide under various controlled stress conditions - Ahmed Gedawy; Hani Al-Salami; Crispin R. Dass (Saudi Pharmaceutical Journal, 2020)
The antidiabetic drugs metformin, gliclazide and glipizide have been widely used and studied in terms of pharmacological and antidiabetic effects, and their individual stability has been studied in the literature. However, the drugs’ combined stability profiling remains poorly understood, and hence the aim of this study was to investigate the collective stability profiling of different combinations at various controlled conditions. Degradation assessments were carried out on metformin, glipizide and gliclazide by applying a stability-indicating HPLC method that was developed and validated in accordance with ICH guidelines. Glipizide, gliclazide, metformin and the binary mixtures (metformin/glipizide and metformin/gliclazide) were subjected to different forced degradation conditions and were detected at 227 nm by an isocratic separation on an Alltima CN column (250 mm × 4.6 mm × 5µ) utilizing a mobile phase that consists of 20 mM ammonium formate buffer (pH 3.5) and acetonitrile at a ratio of (45:55, v/v). The method is linear (R2 = 0.9999) at the concentration range 2.5–150 µg/ml for metformin and 1.25–150 µg/ml for sulfonylureas respectively and offers a specific and sensitive tool for their determination in <10 min chromatographic run. All drug peaks were sharp and well separated. Stress degradation revealed that metformin has a remarkable sensitivity to alkaline stress, glipizide was more sensitive to thermal degradation while gliclazide exhibited almost full degradation in acidic, alkaline and oxidative stress conditions. Keywords: Diabetes, Metformin, Gliclazide, Glipizide, Stability, Stress